The Impact of Digital Banking Service Quality on Customer’s Satisfaction and Customer’s Retention during Pandemic Covid-19 - Jinaratand , Veerasak (Dhammathas Academic Journal, 2022)
The objective of this research is to propose the approach of the impact of digital banking service quality on customer’s satisfaction and customer’s retention. The researcher developed 34 items of a questionnaire and collected the sample of bank branch customer in the North Eastern of Thailand. Multi-regression analysis was use to analyze the data. The research results found that: the four development approaches are service port development, easy to use, interoperability and reliability. These four approaches influenced in predicting simultaneously on satisfaction 66% and on customer retention 59%. However, customer’s satisfaction also influenced on customer’s retention at high level, R2 = .74.